2009
DOI: 10.1111/j.1600-6143.2009.02560.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation Using Donation After Cardiac Death Donors: Long-Term Follow-Up from a Single Center

Abstract: There is a lack of universally accepted clinical parameters to guide the utilization of donation after cardiac death (DCD) donor livers and it is unclear as to which patients would benefit most from these organs. We reviewed our experience in 141 patients who underwent liver transplantation using DCD allografts from 1993 to 2007. Patient outcomes were analyzed in comparison to a matched cohort of 282 patients who received livers from donation after brain death (DBD) donors. Patient survival was similar, but 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
286
2
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 303 publications
(309 citation statements)
references
References 23 publications
15
286
2
2
Order By: Relevance
“…The incidence of IC was associated with a 53% increase (P = .001) in 1-year posttransplant costs, and retransplant was associated with a 107% increase (P < .001) in 1-year posttransplant costs. These data were consistent with those of De Vera and associates, 16 who examined 141 DCD and 282 DBD transplants and observed that the costs of DCD were 20% higher for the index admission. In addition, van der Hilst and coworkers 73 reported that the cost per life-year for DBD was €88 913 compared with €112 376 for DCD, and this difference was statistically significant.…”
Section: Donation After Cardiac Death Costs and Resource Utilizationsupporting
confidence: 81%
See 4 more Smart Citations
“…The incidence of IC was associated with a 53% increase (P = .001) in 1-year posttransplant costs, and retransplant was associated with a 107% increase (P < .001) in 1-year posttransplant costs. These data were consistent with those of De Vera and associates, 16 who examined 141 DCD and 282 DBD transplants and observed that the costs of DCD were 20% higher for the index admission. In addition, van der Hilst and coworkers 73 reported that the cost per life-year for DBD was €88 913 compared with €112 376 for DCD, and this difference was statistically significant.…”
Section: Donation After Cardiac Death Costs and Resource Utilizationsupporting
confidence: 81%
“…11 Pine and associates. 15 However, other reports have yielded inconsistent results; de Vera and coworkers 16 and Skaro and coworkers 17 reported that patient survival was similar for DCD and DBD recipients but that graft survival was significantly lower in DCD than DBD recipients. In addition, relevant to this investigation, several single-institution studies have failed to identify differences in graft and patient survival rates between DCD and DBD livers.…”
Section: Single-center Studies Of Donation After Cardiac Death Liver mentioning
confidence: 84%
See 3 more Smart Citations